Tantangan Mitigasi Risiko Bencana Banjir Di Kota Makassar: Evaluasi Dan Rekomendasi Kebijakan Adaptif - Aljuridaa, A.M.Azhar; Anirwan, Anirwan (JIAP (Jurnal Ilmu Administrasi Publik), 2025)
The urgency of this research highlights the need for effective solutions to reduce the vulnerability of Makassar City residents to the risk of flood disasters, which consistently result in significant impacts on the lives and security of affected communities. The aim of this research is to evaluate the effectiveness of flood disaster risk mitigation policies that have been implemented in Makassar City and identify the main inhibiting factors in their implementation, including formulating adaptive policies that are responsive to these challenges. This research uses a qualitative approach with data collection sourced from interviews, documentation and observations. The data obtained was then coded with Nvivo 12 Plus. These findings indicate that the effectiveness of flood disaster risk mitigation policies in Makassar City is still hampered by several factors, including weak coordination between the government, developers and the community, as well as inconsistent law enforcement regarding land conversion. Inadequate drainage infrastructure and lack of public awareness are also challenges. To overcome this problem, responsive adaptive policies are needed, including increased cross-sector cooperation, stricter law enforcement, infrastructure maintenance, and more inclusive socialization programs. This holistic approach is expected to increase the resilience of Makassar City to the threat of flooding in the future.